Corporate image determinants and the role of attitudes in direct selling companies - Rattanaphan, Prasit (2014)
Frauds and internet scams have tarnished the image of the direct selling company scams in recent years, and many around the world hold a negative attitude about the direct selling business. This negative corporate image has also been triggered by illegal pyramid schemes, lack of corporate social responsibility and confused brand architecture. Hence, the main objective of this study is to examine the antecedents of corporate image in direct selling companies in Thailand through determining the direct and indirect factors affecting corporate image of these companies. A total of 900 questionnaires was distributed to direct selling customers, and 612 were collected back, representing a response rate of 68%. After deleting missing values and outliers, the final 532 usable questionnaires were analysed using structural equation modelling (SEM). This study found that four predictors were significant factors with respect to corporate image; these were internet marketing, corporate social responsibility, trust and attitude. The results also found that two predictors were salient underlying factors that predict customer attitude; these were perceived value and trust. Finally, a mediating effect of attitude between all linkages and corporate image was found to be a full mediator for linkages between perceived value and corporate image. However, attitude was a partial mediator when tested for linkage between trust and corporate image. The study is based upon the attitude toward corporate image as an essential element to the success of direct selling companies and several factors as antecedents, contributing to the enhancement of corporate image among the direct selling companies.